2013
DOI: 10.1007/s00114-013-1011-z
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific and female host-biased ectophoresy in the roundworm Caenorhabditis japonica

Abstract: Caenorhabditis japonica is a bacteriophagous nematode species that was discovered on the semi-social burrower bug, Parastrachia japonensis, which demonstrates egg-guarding and provisioning behaviors. To understand the life history of C. japonica in relation to P. japonensis, we demonstrated the specificity of this association and fluctuations in nematode number on the insect throughout the year. C. japonica dauer larvae (DL), larvae in a nonfeeding diapause stage, were predominantly found as clumps on the adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…By contrast, Caenorhabditis japonica, a gonochoristic (i.e. dioecious) species endemic to Japan, forms a specialized phoretic association with its dispersal host, the shield bug Parastrachia japonensis, such that the nematode life cycle synchronizes with that of the insect [39]. The shield bug is also a specialist species, feeding only on the fruits of the tree Schoepfia jasminodora, and having synchronized its own life cycle such that its reproductive period matches fruit availability [40].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, Caenorhabditis japonica, a gonochoristic (i.e. dioecious) species endemic to Japan, forms a specialized phoretic association with its dispersal host, the shield bug Parastrachia japonensis, such that the nematode life cycle synchronizes with that of the insect [39]. The shield bug is also a specialist species, feeding only on the fruits of the tree Schoepfia jasminodora, and having synchronized its own life cycle such that its reproductive period matches fruit availability [40].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we found that C. japonica forms a species-specific and female-host biased phoretic/necromenic association with P. japonensis (Okumura et al, 2013a, b;Yoshiga et al, 2013). The survivorship of C. japonica DL is maintained at high levels over months on P. japonensis while it is low without P. japonensis (Tanaka et al, 2010b(Tanaka et al, , 2012.…”
Section: Discussionmentioning
confidence: 94%
“…Adult P. (Yoshiga et al, 2013). Erthesina fullo was selected because it was a similar size to that of P. japonensis and it was readily available.…”
Section: Insectsmentioning
confidence: 99%